2018
DOI: 10.2217/epi-2017-0079
|View full text |Cite
|
Sign up to set email alerts
|

Circular RNA Expression in Ovarian Endometriosis

Abstract: CircRNAs are differentially expressed in endometriosis, which might be related with pathogenesis of endometriosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
14
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 40 publications
2
14
0
Order By: Relevance
“…The basic characters of the DE circRNAs were largely in accordance with other diseases and cell types in chromosomal distribution, categories and length [ 48 , 49 ]. In our study, we found the number of up-regulated circRNAs (912/1365) was higher than that of down-regulated circRNAs (453/1365), and this result is in accordance with the circRNA profiles in some other diseases and cell types, such as in radioresistant esophageal cancer cells [ 50 ], but is different than the circRNA profiles in 7-month-old senescence accelerated mouse prone 8 (SAMP8) model brains [ 51 ] and other diseases [ 52 ].…”
Section: Discussionsupporting
confidence: 58%
“…The basic characters of the DE circRNAs were largely in accordance with other diseases and cell types in chromosomal distribution, categories and length [ 48 , 49 ]. In our study, we found the number of up-regulated circRNAs (912/1365) was higher than that of down-regulated circRNAs (453/1365), and this result is in accordance with the circRNA profiles in some other diseases and cell types, such as in radioresistant esophageal cancer cells [ 50 ], but is different than the circRNA profiles in 7-month-old senescence accelerated mouse prone 8 (SAMP8) model brains [ 51 ] and other diseases [ 52 ].…”
Section: Discussionsupporting
confidence: 58%
“…In this study, we investigated circRNA expression profiles in ecEM compared with euEM of endometriosis patients and identified 294 differentially expressed circRNAs, 146 upregulated and 148 downregulated. Most of those dysregulated circRNAs originate from exons or introns which are in accordance with previous researches (Shen et al, ; Xu et al, , ; Zhang, Ren, Xiao, Xia, & Fang, ). It has been reported that both exonic and intronic circRNAs may exert potential functions in gene regulation (Greene et al, ).…”
Section: Discussionsupporting
confidence: 89%
“…In recent years, circRNAs have been the focus of international research, and a large number of circRNAs have been successfully identified in various cell lines and species [19–22]. Furthermore, studies have demonstrated that circRNAs are expressed in eutopic and normal endometrium [23], endometriosis [24], and endometrial cancer [25]. However, there is currently no information available on the expression and function of circRNAs in the developing normal endometrium, or on the differences in circRNAs expression between the RE and PE.…”
Section: Introductionmentioning
confidence: 99%